SINTETIZAÇÃO DE ARQUIVOS TRY A PARTIR DE PADRÕES CLIMÁTICOS CONHECIDOS DE CIDADES PRÓXIMAS - Passos, Aderson; Raviolo, Bruno; Catunda, Natasha; Castro, Nayana; Cordeiro, Karoline; Cardoso, Daniel (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
To avoid unexpected behavior or failure during use, building simulation tools require complete and consistent weather data. However, such data are not always available for the locations where buildings are simulated, and the use of neighboring cities data becomes common. There is, though, a number of uncertainties involved in the behavior of environmental variables when the climate of large urban centers is attributed to nearby localities with different characteristics. The present paper aims to present the process of preparing a weather file for the Pecém Industrial and Port Complex, at 50 km from Fortaleza, Ceará, in order to be used in simulations during the design process of buildings. The synthesis of the file was achieved through the collection and treatment of information measured in loco, the application of recommended models for the estimation of missing data, and the development of an alternative method yet to be validated for the estimation of a Test Reference Year of localities without weather data of several different years.